Burial-induced changes in the seed preferences of carabid beetles (Coleoptera: Carabidae) - Pavel SASKA (European Journal of Entomology, 2019)
Seeds of many species of plants may survive for a long time in the soil and germinate when brought to the surface, but whether they are subsequently eaten by seed predators is unknown. We examined the preferences of three species of carabids (Coleoptera: Carabidae) for 25 species of seeds and determined the difference in palatability between freshly dispersed and those buried for six years. The stability of their preferences was tested using a collection of seeds of different species, each of which was offered fresh or after being buried. Carabid beetles readily accepted previously buried seeds as food. In total, Pseudoophonus rufipes and Amara littorea ate more fresh seeds than previously buried seeds, while the opposite was true for Harpalus affinis. The seeds of some species were even more attractive to carabids after burial than in the fresh state. For all the species of carabids tested, the diet breadth was similar when the beetles were fed fresh or buried seeds, but the preferences for fresh and buried seed of particular species were correlated only in P. rufipes and A. littorea. We measured the seed characteristics (mass and viability) likely to be associated with the loss of attractiveness to carabids during burial. The change in carabid consumption was not related to changes in any of these characteristics. This finding indicates that factors responsible for variation in seed acceptability are complex. This study provides the first conclusive evidence that invertebrate seed predators will feed on seeds from seed banks, although they prefer fresh seeds.